2023
DOI: 10.3390/ph16010130
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Vitamin D Supplementation on COVID-19-Related Intensive Care Hospitalization and Mortality: Definitive Evidence from Meta-Analysis and Trial Sequential Analysis

Abstract: Background: The COVID-19 pandemic represents one of the world’s most important challenges for global public healthcare. Various studies have found an association between severe vitamin D deficiency and COVID-19-related outcomes. Vitamin D plays a crucial role in immune function and inflammation. Recent data have suggested a protective role of vitamin D in COVID-19-related health outcomes. The purpose of this meta-analysis and trial sequential analysis (TSA) was to better explain the strength of the association… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 94 publications
0
44
0
1
Order By: Relevance
“…As such, vitamin D is a vital component in the human body that acts as both a vitamin and a steroid hormone. Thus, policies must be created to raise awareness of the community about 25(OH)D in cases of partial or complete closure [50][51][52]. There is a need for multicenter studies with larger populations covering different regions to strengthen and support our results.…”
Section: Discussionmentioning
confidence: 83%
“…As such, vitamin D is a vital component in the human body that acts as both a vitamin and a steroid hormone. Thus, policies must be created to raise awareness of the community about 25(OH)D in cases of partial or complete closure [50][51][52]. There is a need for multicenter studies with larger populations covering different regions to strengthen and support our results.…”
Section: Discussionmentioning
confidence: 83%
“…Numerous evidences con rm vitamin D insu ciency is associated with greater severity of COVID-19 infection, even the more recent Omicron subvariant of COVID-19(46, 47, 48). Vitamin D administration has been found to be associated with less severe COVID-19 and resulted in a decreased risk of death and admission to intensive care units in patients with COVID-19 (49). In addition, fatty acid metabolism is a crucial event for many viruses to complete their life cycle, and a common consequence of infection by many viruses is to change the nature of lipid metabolism usually from fatty acid oxidation to fatty acid synthesis (50).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to preventive lower dose supplementation, clinical intervention trials with higher doses of vitamin D in hospitalized COVID-19 patients revealed some positive meta-analytical evidence especially on the risk for ICU admission [ 83 , 85 , 91 , 92 , 93 ] although not all meta-analyses showed significant beneficial effects [ 87 , 89 ] ( Table 1 ). In addition, it is suggested that COVID-19 patients may rather benefit from receiving a daily or maintained in time vitamin D dose in contrast to a single vitamin D dose, which does not seem to have any effect on the health status of the patients studied [ 121 , 122 ].…”
Section: Selected Nutrients and Covid-19mentioning
confidence: 99%